Analysis of the impact of referral-based recruitment on job attitudes and turnover in temporary agency workers. Issue 1 (2nd January 2018) - González, Luis; Rivarés, Lorenzo
Abstract : Purpose: The purpose of this paper is to analyse the referral-based recruitment process in temporary work agencies (TWA) and its influence on workers' attitudes and turnover. Design/methodology/approach: By means of a quasi-experimental design with equivalent groups and repeated measures, differences in attitudes -group commitment, task commitment, group satisfaction, general job satisfaction and job involvement- and turnover in a group of workers recruited by the TWA through the "bring a friend" procedure based on employee referrals and in another group comprising workers not recruited through employee referrals are studied. Findings: The results obtained show that workers recruited through employee referrals by the TWA are characterized by having greater group commitment, task commitment, task satisfaction, general job satisfaction and turnover than employees not recruited through employee referrals. These differences are explained on the basis of expectations and the feeling of obligation generated in the recruitment process. Research limitations/implications: The sample size is an element to take into account when valuing the obtained results. Moreover, the effects of the recruitment programs with employee referral on the TWA should be analyze on more qualified jobs. Furthermore, they should be also evaluated if the effects on the attitudes stay the same in longer periods. Originality/value: This is the first paper to examine the impact of the employee-referral-based recruitment method known as "bring a friend" on attitudes – group commitment, task commitment, group satisfaction, general job satisfaction, and job involvement – and turnover of employees when used by TWA. Likewise, we want highlight the fact that this is a longitudinal research study.